Performance analysis of slotted ALOHA in RFID system / Nazmi Azman - Azman, Nazmi (2014)
ALOHAnet or simply ALOHA is a pioneered computer networking system that is developed at the University of Hawaii. The function of ALOHA is to broadcast packets from outbound channel to inbound channel by tackling packet collisions between two clients. In this paper, pure and slotted ALOHA is being simulated to evaluate the performance of both. This study adds the understanding on how a mathematical modeling applied to RFID system. The throughput displays the rate of transmission attempts multiplied by the probability of success scaling the higher the better. The simulation is done using the OPNET Modeller 16.0 and the results show that slotted ALOHA has better throughput performance than pure ALOHA.